Dysoxylum grande hiern as a potential source of biologically active constituents - Low, Kok Wah (2012)
Dysoxylum grande was chosen to be studied due to the lack of reported scientific investigations on the plant and interesting phytochemical findings on another plant of the same genus, Dysoxylum acutangulum. Two biological activities; antiacetylcholinesterase and ichthyotoxicity were used as the bioassay in guiding the fractionation step. As a result, nine compounds were isolated from the ichthyotoxic EtOAc leaves fraction. Among them, eight were identified as new compounds named as 20S,24R-epoxy-7 ,25-dihydroxy-3,4-secodammar-4(28)-en-3-oic acid (CP1), grandol A (CP2), grandol B (CP3), grandol C (CP4), grandol D (CP5), grandol E (CP8), grandol F (CP9) and grandol G (CP10) and the known compound was identified as -sitosteryl- -D-glucopyranoside (CP11). All new compounds were identified based on thorough analysis of spectroscopic data including 1D and 2D NMR. The structure for the known compound was established by spectral data analyses and by comparison with reported investigations. In ichthyotoxic assay carried out on Zebra fish (Danio rerio), EtOAc fraction (leaves) was found to possess significant ichthyotoxicity compared to other fractions. However, the isolated pure compounds did not provide any IC50 values for the ichtyotoxicity test due to their limited amounts. All compounds were tested for anti-acetylcholinesterase activity using Thin Layer Chromatography (TLC)-bioautography with fast blue B salt. Only grandol A (CP2) and grandol B (CP3) showed positive results. However, the obtained IC50 for both of these compounds, grandol A (CP2) and B (CP3), using Ellman’s method was not significant (>200 μg/mL).